Evaluation of the influence of surface and subsurface acidity correction methodologies on soil compaction in agropastoral systems under no-till - Barbosa Borges, Wander Luis; Hipólito, Jorge Luiz; Piantra, Luan Carlos; Dalto de Souza, Isabela Malaquias [UNESP]; Sporch, Helimar Balarone da Silva; Gatto Juliano, Pedro Henrique [UNESP]; Fuzaro Rodrigues, Letícia Nayara [UNESP] (Wiley, 2024)
Surface and subsurface acidity and soil compaction restrict root exploration and impair crop yields in agropastoral systems under no-till. To support the development of surface and subsurface acidity correction methodologies that can decrease soil compaction in agropastoral systems under no-till, this study tested the following hypotheses: (a) the incorporation of limestone with plowing and harrowing (conventional tillage) for surface and subsurface acidity correction decreases soil compaction in agropastoral systems under no-till, (b) the subsurface application of hydrated lime with a shank subsoiler-fertilizer (minimum tillage) for surface and subsurface acidity correction decreases soil compaction in agropastoral systems under no-till, and (c) the surface application of Ca compounds (no tillage) for surface and subsurface acidity correction increases soil compaction in agropastoral systems under no-till. In a field experiment in an agropastoral system under no-till in an Arenic Hapludalf in Brazil, the abilities of three application management methodologies (no tillage, conventional tillage, and minimum tillage) for three Ca compounds (limestone, phosphogypsum, and hydrated lime) to ameliorate acidity in the surface and subsurface layers and decrease soil compaction were evaluated. The experimental design was a randomized complete block with four replications. The results support the following conclusions: (a) the incorporation of limestone with plowing and harrowing does not decrease soil compaction in agropastoral systems under no-till; (b) the subsurface application of hydrated lime with a shank subsoiler-fertilizer does not decrease soil compaction in agropastoral systems under no-till; and (c) the surface application of limestone does not increase soil compaction in agropastoral systems under no-till.